Revitalization of facial skin based on preparations of patient own blood (Journal of Medical Science, 2017)
Aging is a natural, unavoidable physiological process of every human being. Aesthetic medicine, a rapidly growing on field of medicine, slows down this process. Autonomic mezotherapy is a specific type of needle mezotherapy using autologous platelets suspended in a small amount of plasma. Possibilities of use of blood preparations were discussed using 9 items of national literature and 5 foreign reports. The role of the plaques is not only a hemostatic function but also a function of cellular repair by the content of biologically active substances. The biostimulating effect consists in the activation of different cell types by growth factors. The technological change of the gel formulation creates new possibilities for the extension of aesthetic medicine.